Poverty measures, dimensions and some strategies for its reduction in the Caribbean - Gafar, John (2002)
Traces the development of poverty studies and discusses some of its statistical measures. Surveys the evidence of poverty worldwide and discusses some strategies applicable for the Caribbean countries. Provides concluding comments and observations regarding ethnic conflicts and poverty that is creating a chasm in Guyana.